"Me" versus "We" in moral dilemmas: Group composition and social influence effects on group utilitarianism. (10th June 2020) - Curşeu, Petru Lucian; Fodor, Oana C.; A. Pavelea, Anișoara; Meslec, Nicoleta
Abstract: The paper is one of the first empirical attempts that builds on the moral dilemmas and group rationality literature to explore the way in which group composition with respect to group members' individual choices in moral dilemmas and social influence processes impact on group moral choices. First individually and then, in small groups, 221 participants were asked to decide on 10 moral dilemmas. Our results show that emergent group level utilitarianism is higher than the average individual utilitarianism, yet, lower than the highest individual utilitarianism within groups. We also show that average individual utilitarianism positively predicts group utilitarianism while group fragmentation in individual utilitarianism has a negative effect on group utilitarianism. Next to group composition, minority influence processes explain additional variance in group utilitarianism, cognitive dissent having a positive influence, while normative deviance a negative influence on group utilitarianism. Majority influence has no significant influence on group utilitarianism. Finally, our results show that the relationship between group fragmentation in individual utilitarianism and emergent group utilitarianism is mediated by the two forms of minority influence.